KUFRI THAR-1: A NEW WATER-USE EFFICIENT POTATO VARIETY FOR LOW WATER AVAILABILITY AREAS IN MIDDLE GANGETIC PLAINS, EAST COAST PLAINS AND HILLS REGION IN INDIA - Kumar, Devendra; Minhas, JS; Gupta, VK; Rawal, Sanjay; Singh, Name; Singh, Brajesh; Malik, Kamlesh; Singh, BP (Potato Journal, 2021)
Kufri Thar-1 is a medium maturing, main season, high yielding water-use efficient, table potato variety suitable for cultivation in low water availability areas. It is a clonal selection from the cross between Kufri Bahar, having high water use efficiency and CP 1785, identified with a high transpiration rate and better water mining capacity. Its plants are tall and vigorous with field resistance to late blight. Its tubers are white, ovoid with shallow to medium eyes, creamy flesh and having good keeping quality. It is fertilizer responsive and capable of yielding 30-35 t/ha under low water (â‰¤ 20%) availability in middle Gangetic plains. Besides, it is also suitable as an early maturing variety (60-75 days) with 16 t/ha under water deficit conditions in the East-coast plains and hills region in India